Laryngeal Hamartoma in a Newborn - Sultana, Jesmin; Nazme, Nure Ishrat; Sarker, Mukta; Chowdhury, Rehana Begum (Journal of Bangladesh College of Physicians and Surgeons, 2017)
We report an interesting case of a neonate presenting immediately after birth with respiratory distress, inspiratory stridor and difficult intubation. During operative microlaryngoscopy, a well-delineated papilloma like elongated supraglottic mass was seen. The patient underwent surgery, and the diagnosis was confirmed histologically. Biopsy revealed tissue compatible with hamartoma including blood vessel, nerve bundle and cartilage plate. The mass was removed by direct laryngoscopy. Neonatal laryngeal hamartomas are extremely rare. In general, an excellent prognosis is associated with these lesions, and the treatment of choice is endoscopic surgical excision. To our knowledge, this is the first description of a neonatal laryngeal hamartoma in Bangladesh. J Bangladesh Coll Phys Surg 2016; 34(3): 172-174